Pilates Reducing Falls Risk Factors in Healthy Older Adults: A Systematic Review and Meta-Analysis - da Silva, Larissa Donatoni; Shiel, Agnes; McIntosh, Caroline (Frontiers in Medicine, 2021)
Background: The main theme of this systematic review and meta-analysis is to synthesize the evidence of randomized controlled trial of evidence of Pilates intervention, in comparison to control groups and other forms of exercise, for falls prevention in healthy older adults. Methods: The following electronic databases were searched up to October 2020; EMBASE, Scopus, Google Scholar, MEDLINE (Ovid), Science Direct, Cochrane, and CINAHL. The recommendations of the Preferred Reporting Items of Systematic Reviews and Meta-Analyses were followed. A PICOS approach was adopted as a framework to formulate the research question and set the inclusion and exclusion criteria. Participants were healthy older adults, defined as older adults who have maintained functional ability, including participants of both genders, those with a falls history, non-fallers, and individuals who were considered to be sedentary or active. Randomized controlled trials studies, written in the English language, from the decade, were included if they focused on specific outcome measures to decrease falls risk; functional mobility, mobility, fear of falling, gait, and postural stability. The PEDro scale was used to assess risk of bias. Results: There were included 12 studies. In total, 702 healthy older adults' participants were included. Pilates showed an effect in mediolateral directions in comparison to control groups (MD = −1.77, 95% CI, −2.84 to −0.70, p = 0.001, heterogeneity: I2 = 3%), mobility (MD = 9.23, 95% CI, 5.74 to 12.73, p < 0.00001, heterogeneity: I2 = 75%) and fear of falling (MD = −8.61, 95% CI, −10.16 to −7.07, p < 0.00001, heterogeneity: I2 = 88%). In relation to other exercises group, Pilates showed positive effects in functional mobility (MD = −1.21, 95% CI, −2.30 to −0.11, p = 0.03, heterogeneity: I2 = 80%), mobility (MD = 3.25, 95% CI, 1.46 to 5.04, p < 0.0004, heterogeneity: I2 = 0%). No evidence of an improvement was found between the groups for dynamic gait index (MD = 2.26, 95% CI, −0.05 to 4.56, p = 0.06, heterogeneity: I2 = 86%), anteroposterior directions of balance (MD = −1.58, 95% CI, −3.74 to −0.59, p = 0.15, heterogeneity: I2 = 51%) and functional mobility when compared to control groups (no exercise) (MD = −1.24, 95% CI, −2.48 to −0.00, p = 0.05, heterogeneity: I2 = 87%). Discussion: Pilates may be effective in decreasing the risk of falls in older adults. Pilates intervention was found to improve functional mobility, mobility, gait, fear of falling and postural stability and therefore there is some evidence to suggest that Pilates reduces certain risk factors for falls in healthy older adults. However, there is an absence of high-quality evidence in regards to the impact of Pilates on reducing falls and further robust RCTs are needed. Systematic Review Registration: [PROSPERO], identifier [CRD42021206134].